Manipulation of expectancy and anxiety in placebo research and their effects on opioid-induced analgesia - Müller, Maike; Bjørkedal, Espen; Kamping, Sandra (The journal of neuroscience, 2012)
Placebo analgesia is the reduction in pain due to the administration of a pharmacologically inert substance or sham treatment. Research has shown that placebo analgesia is triggered by psychosocial factors associated with the treatment context, such as the interaction between therapist and patient,